Penerapan Metode Dynamic Programming dan Fuzzy Linear Programming Dalam Mengoptimasi Keuntungan serta Jumlah Produksi Padi - Simbolon, Haris Miller; Nasution, Putri Khairiah; Mardiningsih, Mardiningsih; Zahedi, Zahedi (Journal of Mathematics, Computations and Statistics, 2024)
The Kebun Sayur Farmers Group, located in Sub-District Sidoarjo 2 Ramunia, Deli Serdang Regency, North Sumatra Province, is a group focused on rice production. Currently, Farmers groups are experiencing a lack of capital which results in limited resources. To overcome these challenges by optimizing inventory and production quantities so as to enable farmers to maximize their profits. Therefore, the methods used in this research are dynamic programming and fuzzy linear programming, with the application of these two methods can overcome existing problems.. The dynamic programming method increases the production of Ciherang rice by 3580 kg, Inpari 32 rice by 2430 kg, and Inpari 49 rice by 2130 kg, with an increase in production of Ciherang rice by 20.87%, Inpari 32 rice by 17.37%, and Inpari 49 rice by 14.76%, with a probability of profit of 8.33%. Using the fuzzy linear programming method, for a tolerance limit of 5%, the profit obtained is Rp 154.573.935,12 with a profit percentage of 4.89% and a λ-cut value of 0.488. If the tolerance limit is set to 10%, the profit obtained is Rp 156.888.371,28 with a profit percentage of 6.46% and a λ-cut value of 0.5